Tumor targeted self-synergistic nanoplatforms for arsenic-sensitized photodynamic therapy. (November 2020) - Yuan, Ping; Fan, Gui-Ling; Zhao, Lin-Ping; Liu, Ling-Shan; Deng, Fu-An; Jiang, Xue-Yan; Hu, Ai-Hua; Yu, Xi-Yong; Chen, A-Li; Cheng, Hong; Li, Shi-Ying
Abstract: Development of antitumor agents with high efficiency and low toxicity is one of the most important goals for biomedical research. However, most traditional therapeutic strategies were limited due to their non-specificity and abnormal tumor microenvironments, causing a poor therapeutic efficiency and severe side effects. In this paper, a tumor targeted self-synergistic nanoplatform (designated as PAO@PCN@HA) was developed for chemotherapy sensitized photodynamic therapy (PDT) against hypoxic tumors. The efficient drug loading of phenylarsine oxide (PAO) in porphyrinic metal organic framework of PCN-224 as well as the surface modification of hyaluronic acid (HA) improved the targeted drug delivery and reduced the side effects of PAO at the therapeutic dose. Particularly, PAO as an arsenical-based chemotherapeutic agent could not only induce cell apoptosis by generating reactive oxygen species (ROS), but also regulate tumor microenvironments to improve the PDT effect of PCN-224 by mitigating hypoxia and consuming cellular GSH. Both in vitro and in vivo investigations confirmed an effective self-synergy of PAO@PCN@HA in hypoxic tumor therapy with a low systemic toxicity. This integration of microenvironment adjustment with tumor targeted self-synergistic mechanism might provide a new insight for the development of arsenic-based antitumor strategy for clinical applications. Graphical abstract: Image, graphical abstract